THE SOCIAL IMPACT OF MICROFINANCE INSTITUTIONS IN EMPOWERING BOTTOM OF THE PYRAMID GROUPS (BoP) - Indriyo, Wahyu; Gultom, Jonathan (Indonesian Journal of Accounting and Governance, 2023)
This article aims to analyze the social impact of Koperasi Kasih Indonesia (KKI) as amicrofinance institution (MFI) in terms of the form of benefits received by its members and how tomeasure them. Conventionally the parameters of range expansion (outreach) in disbursing microcreditare widely used to measure the social impact of MFIs. The more extensive reach also indicates thepotential benefits that can be obtained by Microfinance Institutions (MFIs). Therefore, if it is separatefrom the social mission of the MFI, the target reach will only encourage the commercial motive of theMFI. On the other hand, measuring the social impact of MFIs takes work and requires more funding.This paper is a descriptive case study of Koperasi Kasih Indonesia (KKI) that aims to identify thesocial impact of KKI on its members by using Social Impact Causal Chain model. The results foundthat there are two types of social impacts of KKI, quantitatively and qualitatively. These two impactsalso explain the transformation process of KKI members who originally received benefits from KKImore in material form (tangible) to be more immaterial benefits of KKI (intangible). The research alsofound that there are superior KKI factors such as the commitment to the social mission of KKI whichis implemented in service programs innovatively, supported by organizational governance and valuesinstilled in KKI officers and members strongly.